Perceived workplace ostracism and deviant workplace behavior: The moderating effect of psychological capital - Preena, Gnei Rushna; Janadari, Nadira (Pakistan Journal of Commerce and Social Sciences, 2021)
Many workplaces have paid more attention to employee behavior in a competitive, dynamic, and expanding business environment since it impacts productivity, efficiency, and effectiveness. These employee behaviors can either be positive or negative. Deviant workplace behaviors are such a form of negative behavior that fallouts as a result of workplace ostracism. The degree to which an employee practices any deviant workplace behaviors is determined by his/her level of psychological capital. Hence this study aimed at finding the moderating role of psychological capital on the relationship between perceived workplace ostracism and deviant workplace behaviors among software engineers in the Information Technology (IT) sector in Sri Lanka. Accordingly, the data collection was done from 186 software engineers using the simple random sampling method. Further, the data analysis was done using the Partial Least Squares -Structural Equation Modelling (PLS-SEM) method with Smart-PLS 3software.After the data analysis, the study findings revealed that perceived workplace ostracism positively impacts deviant workplace behavior, and psychological capital moderates the association between perceived workplace ostracism and deviant workplace behavior. Furthermore, the research findings brought valuable theoretical and managerial implications regarding human resources practices that could control workplace ostracism and deviant workplace behaviors while enhancing psychological capital, followed by implications and future research directions.